Pengaruh Transparansi Laporan Keuangan dan Integrasi Laporan Keuangan terhadap Kepatuhan Wajib Pajak yang Dimoderasi oleh Etika Profesi Akuntan - Pita Rizki Handayani; Sihar Tambun (Jurnal Akuntansi dan Pajak, 2022)
Research objectives to prove ethics of the profession management accountant as moderating variable influence over transparency of financial reports and integration of financial reports to taxpayer compliance. This type of research uses a quantitative approach to research. Descriptive quantitative research methods with the presentation of numbers ranging from data collection, data interpretation and exposure to number results. The results showed that 1) financial statements transparency, financial statements integration, and ethics of the management accountant profession had a positive and significant effect on taxpayer compliance and 2) financial statements transparency and financial statements integration moderated by the ethics of the management accountant profession had a positive and significant effect on taxpayer compliance.